Understanding and accounting for relational context is critical for social neuroscience - Clark-Polner, Elizabeth; Clark, Margaret S. (Frontiers in Human Neuroscience, 2014)
Scientists have increasingly turned to the brain and to neuroscience more generally to further an understanding of social and emotional judgments and behavior. Yet, many neuroscientists (certainly not all) do not consider the role of relational context. Moreover, most have not examined the impact of relational context in a manner that takes advantage of conceptual and empirical advances in relationship science. Here we emphasize that: (1) all social behavior takes place, by definition, within the context of a relationship (even if that relationship is a new one with a stranger), and (2) relational context shapes not only social thoughts, feelings and behaviors, but also some seemingly non-social thoughts, feelings and behaviors in profound ways. We define relational context and suggest that accounting for it in the design and interpretation of neuroscience research is essential to the development of a coherent, generalizable neuroscience of social behavior. We make our case in two ways: a) We describe some existing neuroscience research in three substantive areas (perceiving and reacting to others’ emotions, providing help and receiving help) that already has documented the powerful impact of relational context. b) We describe some other neuroscience research from these same areas that has not taken relational context into account. Then, using findings from social and personality psychology, we make a case that different results almost certainly would have been found had the research been conducted in a different relational context. We neither attempt to review all evidence that relational context shapes neuroscience findings nor to put forward a theoretical analysis of all the ways relational context ought to shape neuroscience findings. Our goal is simply to urge greater and more systematic consideration of relational context in neuroscientific research.